The Effect of Financial Literacy (FL), Financial Access (FA), Financial Risk Attitude (FRA) on Business Sustainability (BS): Mediating Role of Local Cultural Innovation (CI) and Moderating Role of Dynamic Capabilities (DCs) (International Journal of Scientific Research and Management (IJSRM), 2025)
The financial competencies are not alone able to ensure sustainability unless backed by cultural and organizational capabilities in the fast-changing business environment. It is crucial to understand the factors that facilitate businesses to become environmentally responsible in today’s dynamic world. Hence, the objective of this study is to develop a model to further examine the impact of Financial Literacy (FL), Financial Access (FA), and the Financial Risk Attitude (FRA) on Business Sustainability (BS). Further, to examine the role of Cultural Innovation (CI) and Business Performance (BP) as mediating and Dynamic Capabilities (DCs) as moderating variable on the relationship of FL, FA, and FRA by integrating Cultural Embeddedness Theory (CET) Resource Based View (RBV) and Diffusion of Innovation (DOI) theory. The study has devised a quantitative research design which employed a structured questionnaire. The data will be collected from the employees working in Micro and Small Medium Enterprises (MSMEs), Malang, Indonesia. Data is recommended to be analysed through Partial least Square-Structural Equation Modelling (PLS-SEM) to assess the direct, mediating, and moderating impact of FL, FA, FRA, BP, and DA on SB. The findings of the study will reveal that FL, FA, FRA impact on BS. Further the results will reveal the mediating CI and BP and moderating role of DCs. Furthermore, the results will be highlighting the importance of integrating different variables into business strategies. The study has contributed to the existing scholarship by integrating CET, RBV, and DOI theories to develop a framework to investigate the impact of different factors on BS. Furthermore, the study has provided integration of DCs and CI to better understand the phenomenon under investigation. By offering a unique understanding of how cultural and financial factors interact with dynamic environments. The study provides a practical and theoretical insight for policymakers, businesses, and MSMEs to foster sustainable business models in developing economies.